PATOLOGI MANAJEMEN PELAYANAN SEKTOR PUBLIK DALAM PROGRAM PEMUTIHAN SURAT KENDARAAN BERMOTOR DI PROVINSI LAMPUNG (Studi Pada SAMSAT Lampung Tengah) - Saputra, Pindo Riski; Aspriani, Octavia; Saputra, Muhammad Aden (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2022)
Participation in supporting national development does not only help the government but the existence of development stakeholders in every layer, greatly determines the success of national development, in this case the involvement of local governments must be able to synergize well with the central government in the implementation of national development, it must be supported by the economy from national income. . The research method that researchers use in this research is descriptive qualitative analysis method. The approach to substantive and formal theories as well as events that exist and are recognized as true. Writing using this method aims to describe the problems studied accurately regarding the facts and causes of the observed phenomena. poor management services to the community, of course this is very deviating from the values ​​and basic rules of a policy implementation process in optimizing public services, in which case the policies made must be successful with good implementation stages, therefore an understanding of pathological problems can be the main basis for SAMSAT in implementing tax administration services within its organizational environment effectively and efficiently.